CLASSIFICATION OF VALUES IN THE CONTEXT OF EDUCATIONAL MANAGEMENT - A. V. Bakuradze (Obrazovanie i Nauka)
The paper emphasizes the relevance of the axiological approach to managerial activities based on identification of key values meaningful for the heads of educational establishments. From the above standpoint the author analyzes the classification of values by Plato, Aristotle, D. Hume, I. Kant, H. Rickert, N. Lossky and other thinkers, and puts forward the four-level hierarchy of managerial values that involves the following successive levels: recourse values; procedural values; work values, efficiency and effectiveness; and human, social and organizational values. The results of retrospective analysis are extrapolated to the activity  of educational establishments wherein the values of educational management are regarded as social values. The range of the given values might differ depending on cultural, social and other peculiarities that should be taken into consideration by heads of educational establishments. The above distinctions lead to the different role evaluation of the natural environment, social institutions, personal rights and freedoms, as well as traditions and innovations in developing the social organizations.